¿El plan de desarrollo distrital Bogotá positiva en lo social es un mito o una realidad? Enfoque hacia el nucleo principal de la sociedad "la familia" (2011)
The current Development Plan Bogotá. DC, was built by objectives which facilitates inter-sectoral and allows crucial to understand that government intervention is the people, the quality of life in all dimensions and at different life stages. At present the Development Plan of Bogota in the family has as goals: to serve 302,500 families with rights violated through access to family and social justice, promotion and restoration of rights, establish a baseline for the exploitation sex boys and girls in Bogotá Address to 5,000 families affected by eviction orders informal settlements and illegal, among other goals that are handled in the district development plan. At district level there is an entity that manages the city's social situation ̈ The District Department of Social Integration ̈, which has measurable goals and projects that reach the community regardless of their ethnicity, gender, creed or socioeconomic providing assistance needed to improve their quality of life, as is the case of kindergartens, soup kitchens, shelters for the elderly, street dweller care, curator of family, CIF, among others